ANALISIS KESALAHAN SISWA DALAM MENYELESAIKAN SOAL PADA MATERI OPERASI MATRIKS DI SMA YABT MANOKWARI - DEWI WAHYUNINGSIH (Jurnal Perspektif Pendidikan, 2020)
This research aims to describe the types and causes of mistakes made by grade XI IPA students in YABT Manokwari senior high school in resolving questions about matrix operating materials. The type of research used in this research is qualitative descriptive, this type of research is part of qualitative research. In the research subjects, there were as many as 32 students given a description test, then grouped into 3 categories for interviews. The results of the research obtained that the mistakes made by students are as follows: (i) error in organizing data amounted to 29.2%; (ii) a draft error amounted to 37.5%; (iii) error due to carelessness amounted to 54.2%; and (iv) errors in drawing conclusions amounted to 58.3%. The caused of the error was because students were less thorough in reading and interpreting questions, lack of understanding of the concepts to be used, less thorough in doing calculations and rushing so they forgot to conclude the final answer.